IV. CO‐CONSTRUCTION OF ATTACHMENT REPRESENTATIONS AND AFFECT‐REGULATING COGNITIONS: THE ROLE OF MATERNAL ATTACHMENT SECURITY. Issue 4 (5th December 2018) - Waters, Harriet S.; Steiner, Michelle A.; Zaman, Widaad; Apetroaia, Adela; Crowell, Judith A.
ABSTRACT: This study focused on the role of maternal co‐construction skills in building attachment relevant representations in early childhood. Thirty‐four mothers and their 4‐ to 5‐year‐old children were presented with two co‐construction tasks, one an attachment storytelling task, the other an affect discussion task about emotion‐laden situations. Maternal co‐construction skills were assessed with several scales that scored the quality of the co‐construction partnership, the mother's skill in prompting elaboration, and helping build an explanatory framework. Mothers completed the Attachment Script Assessment (ASA) and the Adult Attachment Interview (AAI) as well. Results indicated that mothers' secure base script knowledge (ASA) was significantly related to communication effectiveness, encouraging elaboration of storylines, and using open‐ended and why questions. Maternal AAI coherence showed similar relations to co‐construction support.